STRATEGI KOMUNIKASI WALI NAGARI DALAM MENGATASI KENAKALAN REMAJA DI NAGARI LUBUAK GADANG KECAMATAN MAPAT TUNGGUL KABUPATEN PASAMAN - Reynaldy Rifanda; Asrul Harahap (Jurnal Komunikasi, 2025)
Planning and managing towards a goal is the definition of strategy. However, to achieve this goal, the methodology does not serve as a guide that will determine the direction of the business, but can indicate a functional strategy. a strategy designed with the aim of influencing a wider range of human behavior by incorporating new ideas. There is also a correspondence system which is the best combination of all correspondence components starting from the communicator, message, beneficiary channel, and impact intended to achieve the purpose of the correspondence. Adolescent misconduct is an act that does not heed norms, decisions or regulations that apply in public, which is committed during adolescence or the transition period from adolescence to adulthood. Teenage misbehavior includes all behavior that deviates from legal or strict standards carried out by teenagers, this behavior can harm themselves or others. The exploration carried out was field research using subjective elucidation techniques. Information gathering procedures are carried out using methods such as perception, meetings and documentation. The information checking procedure uses strategies such as editing information (reducing information), displaying information (information show), and carrying out determination and checking (ending/confirmation). Judging from the impact caused by the exploration, there are several types of correspondence techniques for nagari guards in dealing with juvenile delinquency, especially correspondence procedures that are successful in dealing with juvenile delinquency. Direct correspondence between the Wali Nagari and the local area, as well as using firm messages and priorities, providing advice, direction and guidance to the younger generation. Activities such as positive activities, exposure to regional culture, welcoming the younger generation to tourist destination cities, and arranging Tahfiz huts are one way to develop rigorous learning and rigorous quality